Effectiveness of Education Program on Secondary School Teachers Psycho-Social Changes with Menopause in Baghdad City - Fawzi, Ishraq; ali, rabea (Iraqi National Journal of Nursing Specialties, 2019)
Objective: To assess the effect of education program on psychological and social changes of secondary school teachers with menopause. Method: A quasi-experimental design is carried out with the application of a pre- post –test for menopause secondary school teacher’s bio-psychosocial changes. Non-probability sample consists of (60 female teachers) (40) teachers from Al- Rusafa first Education Directorate secondary schools, and (20) teachers from Al- Karkh third Education Directorate secondary schools. The sample was exposed to pretest, educational program, and posttest. Data were collected through the utilization of the study instrument (the questionnaire) and application of bio-psychosocial education program on secondary school teachers with menopause from the period (2nd September 2018 through 24th February 2019). Content validity of the program obtained by panel of (14) experts. the reliability of the instruments is obtained through the (test &retest ). Data are analyzed through the application of descriptive and inferential statistical data analysis approach. Results: Results shows that all of studied items regarding psychological and social changes has a moderate mean scores and relative sufficiency evaluation before applying the educational program, except in sharing with the family social sub domain’s items , which were assigned a low mean scores and relative sufficiency responses initially. In the other hand, most of studied items has a good improvements and a proved high and moderate mean scores and relative sufficiency of evaluation after implementation of the educational program. As well as, comparisons significant related to pre- post periods , which registered a highly significant differences at P<0.01. Recommendation: The study recommends an emphasis on health education program for women to increase their awareness about the importance of menopausal changes, and how to cope.